Organizational Behavior in Special Education Schools within Arab Society in Israel: Navigating Challenges and Leveraging Opportunities - Tanti, Rajesh (Journal of Research in Vocational Education, 2026)
Special education schools in Israel’s Arab society operate within a complex matrix of cultural, social, and structural dynamics. This article explores the intricacies of organizational behavior within these institutions, emphasizing leadership practices, internal communication, staff dynamics, stigma, and innovation. New sections explore gendered organizational roles, the impact of religious- cultural norms, and digital adaptation in schools. The article concludes with recommendations for culturally informed organizational development to enhance educational equity.